Peningkatan Kinerja Sumber Daya Manusia Karyawan PT. JPT Jatidiri Trans Cabang Surabaya - Agil Gusrian Neldi; Soedarmanto; Mudayat (Yos Soedarso Economic Journal (YEJ), 2024)
This research was conducted to analyze the improvement in human resource performance at PT. JPT Jatidiri Trans Surabaya Branch. The type of data used in this research is quantitative. The population in this study were employees of PT JPT Jatidiri Trans Surabaya Branch while the sample consisted of 30 respondents using a saturated sampling technique. The data used is obtained from primary data and secondary data. This data collection technique was carried out by distributing questionnaires. The analysis technique used is multiple linear regression analysis. The results of this research show that leadership style has a partially significant effect on employee performance. The implications that occur in this research are that the application of a democratic and moralist leadership style has proven to be influential in improving employee performance, motivation has a partially significant effect on employee performance, motivation is a very important variable. Dominant in improving employee performance. The implications of this research are that the company implements divisional exchange management once every 2 years so that it motivates employees to expand their experience. Work discipline has a partially significant effect on employee performance. The implications that occur in this research are that work must be done on time and comply with regulations. company, consistently maintain company services. Leadership style, motivation and work discipline simultaneously have a significant effect on employee performance.